Unconventional Monetary Policy, Disruptions in the Banking Sector and Banking Sector Efficacy: An ARDL and Bound Testing Applied to the Tunisian Banking Sector - Marzouki, Mohamed Miras (Journal of Reviews on Global Economics, 2025)
A longstanding debate is raised about whether banking sector is efficacious in the meaning it helps respond to investors financing requirements and whether it serves the conduct of monetary policy in its conventional formulation. There are much concerns also about the alternatives of monetary policy conduct when the interest rate channel transmission mechanism does no longer work in terms of effectiveness of monetary policy and how to step aside credit supply insufficiencies and disruptions in order to respond to excess credit demand. This article provides an assessment of the relevance of unconventional monetary policy to deal with the issue of the vicious role played by the credit sector depicted from its failure to fulfill banking sector efficacy due to an excessive search for yield motivation and extreme awareness from systemic risk. For that sake we run an ARDL and Bound test to the data collected on the Tunisian banking sector and show that Banking sector efficacy is affected in the short run by Fisherian sensitivity another expression of the impact of inflation on real activity and banking sector specificities and in the long run it is affected by the impact of inflation on real activity and business cycle effects expressed in terms of sensitivities of Credit supply and demand to output gap. We highlight that over the long run, Banking specificities do no longer matter and banking sector efficacy is not at all affected by Monetary policy because of nominal rigidities and monopolistic competition and backward oriented expectations that divert the pass through effect of monetary policy as the pricing of loans and is exclusively tributary on the search for yield motivation and the agency costs that result in a non competitive price of risk premiums that do not translate the transmission of monetary policy. We conclude that the behavior of the banking sector is vicious because it conveys importance exclusively to the search for yield motivation, profitability and to the mitigation of systemic risk and does not play any role in the promotion of local investment which is a pillar of economic performance and growth. We hence propose the Credit easing as an unconventional monetary policy that can step aside the hindrance of an inelastic credit supply through modifying asset prices and thereby improving attractiveness of assets to the banking sector and forcing financing through credit allocation but warn from the difficulties that might result from unconventional monetary policy in terms of inability to withdraw from the perturbation and gauge discretionary policy accurately.